In the Name of Entrepreneurship? The Logic and Effects of Special Regulatory Treatment for Small Business - Gates, Susan M. (RAND Corporation, 2007)
What are the differential effects of regulation and policy on small businesses? What is the impact of special regulatory treatment for small businesses? This book sheds light on these issues through analysis of the regulatory and public policy environment with regard to small businesses, including focused studies in four key areas: health insurance, workplace safety, corporate governance, and business organization.